COMPARATIVE STUDY OF FRICTION STIR WELDING WITH A FIXED SHOULDER (Global Journal of Advanced Engineering Technologies and Sciences, 2016)
Friction stir welding is an innovative solid-state joining technique that has been conventionally found to produce high quality joints in the range of 200-2000 rpm, it has demonstrated that friction stir welding and processing with much higher spindle speeds is possible. The principle advantage of operating at higher rotation speeds is the ability to reduce the spindle torque and forging loads. The primary disadvantage is that reduced forging loads create more opportunities for the formation of weld defects like voids, wormholes and increased porosity. One way to overcome that challenge is through the introduction of a non-rotating shoulder surrounding the rotating pin, in order to maintain the necessary forging loads to prevent weld defects. This paper details the principal resultant metallurgy with comparisons made to representative traditional friction stir welded metallurgy. The resultant mechanical properties and process force analysis of the welded joints is also provided.